THE EFFECT OF PREMARITAL SEXUAL HEALTH EDUCATION ON ADOLESCENTS' KNOWLEDGE AND ATTITUDES AT MADRASAH ALIYAH PUTRI AL-KHOIROT MALANG - Putra, Fetreo Negeo; Nengrum, Lilis Sulistya; Hilmiyah, Alfi; Samudera, Wahyu Sukma (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2025)
Background: Adolescents are a vulnerable group to sexual problems, which can lead to an increase in unwanted pregnancies and early marriages due to a lack of knowledge and appropriate attitudes. Premarital sexual health education serves as an important preventive effort to improve healthy knowledge and attitudes related to sexuality. Purpose: This study aims to examine the effect of premarital sexual health education on the knowledge and attitudes of adolescents at Madrasah Aliyah Putri AL-Khoirot Malang. Methods: This study used a pre-experimental design with a one-group pretest-posttest approach. A total of 67 students were selected using stratified random sampling. The instruments used were knowledge and attitude questionnaires, and the data were analyzed using the Wilcoxon test. Results: The findings revealed a significant increase in knowledge and attitude scores after the educational intervention (p < 0.05). Conclusion: Premarital sexual health education significantly improves adolescents’ knowledge and attitudes toward healthy sexual behavior. Educational institutions are encouraged to integrate comprehensive sexual health education programs to prevent risky sexual behavior among youth.